Influence of a rural interprofessional education placement on the rural health workforce: working in primary care, rural settings, and with Māori - Sue Pullon; Gordon Purdie; Lesley Gray; Eileen McKinlay; Melanie Brown; Ben Darlow (CSIRO Publishing, 2023)
Introduction Pre-registration interprofessional rural immersion programmes provide students with first-hand insight into challenges faced in rural clinical practice and can influence future practice intentions. The impact of short rural and hauora Māori interdisciplinary placements on early healthcare careers is unknown. Aim Explore whether a 5-week rural interprofessional education programme influenced graduates' choices to work in primary care, rurally, and with Māori patients. Methods We conducted a survey-based, non-randomised trial of graduates from eight healthcare disciplines who did (n = 132) and did not (n = 479) attend the Tairāwhiti interprofessional education rural programme with hauora Māori placements. Participants were surveyed at 1-, 2-, and 3-years' post-registration. Self-reported practice location and vocation were analysed with mixed-model logistic regression. Free-text comments were analysed with Template Analysis. Results We did not identify any measurable impact on rural or community workforce participation at 3-years' post-registration. Free-text analysis indicated that a short rural interprofessional immersion placement had long-term self-perceived impacts on desire and skills to work in rural locations, and on desire and ability to work with Māori and embrace Māori models of health. Discussion Our study suggests that short rural immersion placements do not increase rural workforce participation during early healthcare careers. Three-years' post-graduation may be too early to determine whether rural placements help to address rural health workforce needs. Reports from rural placement participants of increased ability to care for people from rural backgrounds, even when encountered in a city, suggest that assessment of practice location may not adequately capture the benefits of rural placement programmes.